Susceptibility of Plutella xylostella (L.) to Bacillus thuringiensis Berliner strains - Viana, Cácia L. T. P.; De Bortoli, Sergio A.; Pedroso, Elizabeth C.; Vacari, Alessandra M. (BioAssay, 2021)
The objective was to observe the susceptibility of a population of Plutella xylostella (L.) maintained for 100 generations in laboratory to strains of Bacillus thuringiensis Berliner. The concentrations 9×104, 1.5×105, 6×105, 8×105, 9×105, 1.5×106, 2×106, 3×106, 4.5×106, 6×106, 7.5×106, 9×106, 1.5×107, 2×107, 3×107, 4×107, 4.5×107, 6×107, 7.5×107, 9.5×107, 1.5×108 e 3×108 spores/mL were evaluated for the strains: E1, 49.30A, E2, 1.7L, T3A.259, T3A.140, T08024, E26, E22 and T07. The strains E26, E22 and T07 did not cause mortality for P. xylostella larvae. The P. xylostella larvae have a very high susceptibility pattern to the concentrations evaluated for six strains tested (E1, 49.30A, E2, 1.7L, T3A.259 and T3A.140). Only the T08.024 strain allowed the estimation of lethal concentration that kills 50% of the population (2.7 spores/mL).